1999
DOI: 10.2527/1999.7771679x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for production traits and measures of residual feed intake in large white swine.

Abstract: Production and reproduetive traits in Danish Landrace (LD) and Large White (LW) swine were analysed by restricted maximum likelihood methods to obtain heritabilities as well as genetic and phenotypic correlations. Production traits were: age, backfat thickness (BT), muscle depth (MD) and the ratio BT/MD, adjusted to Standard bodyweight of 85 kg. Reproduction traits were: number of pigs born (NB) and number of pigs weaned (NW) per sow and parity. Heritabilities for age, BT, MD and BT/MD were 0.60, 0.44, 0.51 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
65
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 24 publications
27
65
3
1
Order By: Relevance
“…However, these latter authors did not show any effect on feed intake. In our study, QTL effects on ADG were positively correlated with QTL effects on DFI, which agrees with the genetic correlation between these traits (Johnson et al, 1999). This would imply that the alleles increasing ADG would be linked to alleles increasing DFI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, these latter authors did not show any effect on feed intake. In our study, QTL effects on ADG were positively correlated with QTL effects on DFI, which agrees with the genetic correlation between these traits (Johnson et al, 1999). This would imply that the alleles increasing ADG would be linked to alleles increasing DFI.…”
Section: Discussionsupporting
confidence: 89%
“…QTL for DFI (Duthie et al, 2008) and for tissue composition of the ham (Heuven et al, 2009) in a commercial cross including the PI breed were detected in this same region. Correlations between the effects of the SSC2 QTL on different traits indicated that haplotypes increasing TFI might be physically linked to haplotypes increasing BFT, in the direction of known genetic correlations (Johnson et al, 1999). On the contrary, their correlations with the QTL effects on LMC showed no clear pattern, suggesting that two different loci could segregate in the region.…”
Section: Discussionmentioning
confidence: 96%
“…Our estimated ADFI heritability from 1622 individuals was within the range of values being similar to the range of 0.23–0.66 that has previously been reported for swine (Mrode & Kennedy 1993; Johnson et al . 1999; Suzuki et al . 2005; Hoque et al .…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2002) reported estimates of 8 to 12% for backfat across breeds. Crump et al (1997) reported estimates of 5 and 6% in backfat and ADG, respectively, while Johnson et al (1999) reported Table 2 Levels of significance for the fixed factors the analysis of Mukota pigs reared in a common herd †…”
Section: Discussionmentioning
confidence: 99%